Prevalence of Bovine Anaplasmosis in Malaysian Farms - Althabet Mirwan, Nabil Milad (2003)
The mam objective of this cross sectional study was to determine the prevalence of bovine anaplasmosis in Malaysian farms involving Selangor and Pahang and to determine the potential risk factors related to the seroprevalence. A total of 180 animals from seven dairy farms and 12 beef farms were involved in this study. A questionnaire was used to collect data on cattle health and management practices. Seven dairy and six beef farms participated. Sixty-eight blood samples in heparin from dairy cattle were tested for Anaplasma sp. using Giemsa thin smear and no parasitemia was observed. One hundred and eighty sera from dairy and beef cattle farms were tested for antibodies to A. marginale using competitive enzyme linked immunosorbent assay kit (cELISA kit). The seropositivity of A. marginale was 87.7% (158/180) when a cutoff of > 30% was considered as positive. The seroprevalence of bovine anaplasmosis in smaller farms (30-60 animals) were significantly (p < 0.05) higher at 96.7% compared to bigger farms (> 60 animals) (78.8%). Farm type, breed, age, and sex were not significant factors. There were also no correlation between antibody prevalence status and packed red cell volume, body condition score and rectal temperature in the dairy animals studied.